Microplastic pollution of the Zrafshan river tributary in Samarkand and Navoi regions of the Republic of Uzbekistan - Alijon Khusanov; Ozodbek Sabirov; Yulia Frank; Danil Vorobev; Egor Vorobev; Svetlana Rakhmatullina; Sherzodbek Tashbaev; Sarvinoz Mamatkarimova; Abdumukhtar Yakhyoyev; Mukhammadyusuf Juraev; Ilyas Isakov; Dilyor Karimjonov; et al. (Green Analytical Chemistry)
This study analyzes microplastic pollution of surface waters of the Zarafshan River flowing through the Samarkand and Navoi regions of Uzbekistan. Microplastics pose a serious threat to aquatic ecosystems due to their ubiquity and ability to accumulate toxic substances. In the Central Asian context, the problem of microplastics remains poorly understood, complicating the development of mitigation strategies. The study was conducted in July 2023. Surface water samples were collected using a microsampler equipped with a 330μm mesh. Laboratory processing included oxidation of organic matter with hydrogen peroxide and separation of plastic particles by density separation. Raman spectroscopy was used to identify the polymer composition. According to the results, the concentration of MP particles was 3.22±1.64 units/m3 in the corresponding part of the Zarafshan River in the Navoi region and 2.96±0.78 units/m3 in the Samarkand region. The particles found in the water have a diameter of 0.15 to 3.00 mm. According to the results of the data analysis, a part of the Zarafshan River flowing through the territory of Samarkand and Navoi regions is polluted with plastic particles due to environmental factors. Existing data on microplastic pollution of freshwater ecosystems in Central Asia are fragmentary, which makes it difficult to assess environmental risks and take appropriate measures. The aim of this paper is to assess the level of microplastic pollution in the Zarafshan River and identify the main sources of pollution. The results of the study highlight the need for regular monitoring and the development of effective measures to reduce the level of microplastic pollution in the region.